Kedudukan Royalti sebagai Harta Warisan Perspektif Wahbah Az-Zuhaili - Dinda Aprilia Syalina; Sukiati (CV Global Research Publication, 2026)
The problem addressed stems from the intangible nature of royalties and their uncertain value, as they depend on the future commercial exploitation of a work (future income), which differs from the concept of tangible assets in general. This raises questions regarding their status as an object of inheritance, as seen in the practice of inheriting royalties from the songs created by Papa T Bob to his heirs. This study aims to analyze the position of royalties as inheritance assets (tirkah) from the perspective of Wahbah Az-Zuhaili's thought. This study employs a qualitative method through library research with a normative-conceptual approach. The findings show that Wahbah Az-Zuhaili, in line with the view of the jumhur fuqaha (majority of jurists), categorizes royalties as property (al-māl) because they possess economic value and real benefit despite lacking physical form. The study concludes that royalties are legitimately considered an object of inheritance (tirkah), since the economic right does not cease upon the creator's death but instead transfers to the heirs as huqūq māliyyah (financial rights), in accordance with sharia principles and the Copyright Law. Practically, this study contributes to the development of contemporary Islamic inheritance law concerning the management of intellectual assets in the modern economic era.